In vivo evaluation of hybrid patches composed of PLA based copolymers and collagen/chondroitin sulfate for ligament tissue regeneration. Issue 7 (17th May 2016) - Pinese, Coline; Gagnieu, Christian; Nottelet, Benjamin; Rondot‐Couzin, Capucine; Hunger, Sylvie; Coudane, Jean; Garric, Xavier
Abstract: Biomaterials for soft tissues regeneration should exhibit sufficient mechanical strength, demonstrating a mechanical behavior similar to natural tissues and should also promote tissues ingrowth. This study was aimed at developing new hybrid patches for ligament tissue regeneration by synergistic incorporation of a knitted structure of degradable polymer fibers to provide mechanical strength and of a biomimetic matrix to help injured tissues regeneration. PLA‐ Pluronic ® (PLA‐P) and PLA‐Tetronic ® (PLA‐T) new copolymers were shaped as knitted patches and were associated with collagen I (Coll) and collagen I/chondroitine‐sulfate (Coll CS) 3‐dimensional matrices. In vitro study using ligamentocytes showed the beneficial effects of CS on ligamentocytes proliferation. Hybrid patches were then subcutaneously implanted in rats for 4 and 12 weeks. Despite degradation, patches retained strength to answer the mechanical physiological needs. Tissue integration capacity was assessed with histological studies. We showed that copolymers, associated with collagen and chondroitin sulfate sponge, exhibited very good tissue integration and allowed neotissue synthesis after 12 weeks in vivo . To conclude, PLA‐P/CollCS and PLA‐T/CollCS hybrid patches in terms of structure and composition give good hopes for tendon and ligament regeneration. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1778–1788, 2017.